É inteligente, mas...: perspectivas e formação de professores para as altas habilidades/ superdotação - Oliveira, Fernanda Souza de (2018)
When dealing with topics such as the inclusion of students with special educational needs or special education, we usually attribute such concepts to students with physical, intellectual, or syndrome-related disabilities, most of whom are not people with High Abilities / Giftedness (HA/GN). This work is based on the observation at the HA/GN provided by Joseph Renzulli, theorist present in Brazilian documentation and guidelines. People with HA/GN are those who, in interaction with the environment, present superior abilities compared to the general population. HA/GN can be of the academic type, in which the skills are concentrated in the linguistic or logical-mathematical areas, and, therefore, are more observable in the school environment; or the productive-creative type in which artistic expressions and divergent thinking stand out. Theorists differentiated the categories only for didactic purposes, as it is often possible to find people with characteristics of the two types. The Brazilian legislation referenced in different national documents, as well as in the specific legislation of the State and Municipality of São Paulo on the subject, understands people with HA/GN as a target audience of special education and provides specialized educational assistance (SEA) to all students who need it. However, among teachers, the topic seems to be unknown and it can be observed that there are almost no proposals in which curriculum and/or service issues are discussed in multifunctional resource rooms. In theory, I realize that SEA occurs for students with disabilities, but there are few proposals for serving students with HA/GN. Considering the problem of the lack of teacher training that makes students with HA/GN invisible, the present research was developed to understand how teacher training has contributed to the identification and care of these students in the municipal teaching network. The relevance of this research problem is perceptible both from the theoretical and from the social point of view. As for the first, I understand that the studies about continuing education of teachers in special education and with a specific focus on students with HA/GN have appear more recently and more frequently after 2013, thus showing that it is a silenced topic. Regarding the second point, identifying and analyzing teachers' conceptions about continuing education in special education and directed to students with HA/GN can be of great help both for the improvement of such courses and for teachers who work in this area. The research will be carried out with teachers from the city of São Paulo involved with the presented theme. As a methodological choice for this qualitative research, we propose the reflexive interview mode. The guiding hypothesis of the work is: students with HA/GN do not reach SEA care because they are not easily identified in the regular school classrooms and, therefore, end up with a disadvantage in school